2016
DOI: 10.1155/2016/5939164
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Gait Parameters as Predictors of Lower-Limb Overuse Injuries in Military Training

Abstract: The study objective was to determine whether spatiotemporal gait parameters could predict lower-limb overuse injuries in cohort of combat soldiers during first year of military service. Newly recruited infantry soldiers walked on a treadmill at a 15° incline with a fixed speed of 1.67 m/sec while wearing a standard military vest with a 10 kg load. Stride time variability, stride length variability, step length asymmetry, and the duration of the loading response phase of the gait cycle were measured. Injury dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…For example, measurement of physical fitness using maximal oxygen intake (VO 2 max), which was reported to predict attrition and injuries, can be determined by a simple two-mile or three-mile run time [6,10]. In contrast to simpler evaluation methods, a computerized analysis of gait was used by Springer et al to identify certain specific gait parameters that predicted lower limb injuries among infantry soldiers [20]. Tiggelen et al reported that measurement of isokinetic strength could distinguish between recruits who would or would not develop anterior knee pain [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, measurement of physical fitness using maximal oxygen intake (VO 2 max), which was reported to predict attrition and injuries, can be determined by a simple two-mile or three-mile run time [6,10]. In contrast to simpler evaluation methods, a computerized analysis of gait was used by Springer et al to identify certain specific gait parameters that predicted lower limb injuries among infantry soldiers [20]. Tiggelen et al reported that measurement of isokinetic strength could distinguish between recruits who would or would not develop anterior knee pain [21].…”
Section: Introductionmentioning
confidence: 99%
“…The length of the step was de ned as the anteroposterior distance between the left and right heel markers at each initial contact. The de nitions of spatiotemporal gait parameters presented in this study were the same as in a previous study that investigated lower-limb overuse injuries among military recruits [24]. The stride time variability was calculated as 100 × (stride time SD/mean stride time), the stride length variability was calculated as 100 × (stride length SD/mean stride length), the step length asymmetry was calculated as 100 × ln(right step length/left step length).…”
Section: Gait Assessmentmentioning
confidence: 99%
“…Mokha et al (2016) found asymmetry functional movement screen (FMS) score as a better predictor of musculoskeletal injuries. Springer et al (2016) found that gait analysis can be used in the diagnosis of shoulder overuse injury. Azzam et al (2015) and Whittaker et al (2017) had suggested to focus on high-quality cohort studies to find the most relevant results of movement quality in the prediction of risk of injury.…”
Section: Introductionmentioning
confidence: 99%